ADVANCES IN NOVEL DRUG DELIVERY SYSTEM EMPHASISING FLOATING MICROSPHERES FOR ULCER TREATMENT - Nair, Nikhila. M.; Varghese, Rinu; L., Lekshmi; R., Anitha Lekshmi M.; Abraham, Linku; Nair, Mohana M.; Aniyan, Neema; A., Dr. Shajan (Asian Journal of Pharmaceutical Research and Development, 2016)
The purpose of writing this review on novel drug delivery system with special focus on Floating microspheres was to compile the recent literature on method of preparing the floating microspheres. Ulcers are lesions which is a discontinuity of gastrointestinal mucosa. Various medications are used to treat mild to moderate ulcers. Drugs used to treat ulcers are called anti-ulcer drugs. Floating microspheres prepared by solvent-evaporation method using polymers and solvents whose particle size analysis, scanning electron microscopy, encapsulation efficiency and drug loading, in-vitro release study, stability studies characterization was carried out which showed an improved absorption and bioavailability by retaining the system in stomach for a prolonged period of time. Significant attempts have been made worldwide to explore these systems according to patient requirements, both in terms of therapeutic efficacy and compliance. Floating microspheres as gastro retentive dosage forms precisely control the release rate of target drug to a specific site and facilitate an enormous impact on health care. This review briefly emphasizes on Gastro Retentive Drug Delivery system of anti-ulcer drug. Various categories like antacids, antidiabetic, antifungal and anticancer drugs are formulated into Floating Drug Delivery System. These systems also provide tremendous opportunities in the designing of new controlled and delayed release oral formulations, thus extending the frontier of futuristic pharmaceutical development. In the present review preparation methods, characterization, advantages, applications are discussed.